Membranotropic action of phytodrugs - Gorchakova, N.; Belenichev, I. F.; Harnyk, T.; Shumeyko, O.; Klymenko, O.; Горчакова, Н.; Бєленічев, Ігор Федорович; Гарник, Т.; Шумейко, О.; Клименко, О. (My University, 2023)
Actuality. The article, based on its own research and literature sources, presents data on the effect of herbal medicines, primarily on ion channels. Membranotropic action is also associated with receptors, enzymes, signaling systems. At the same time, the works of recent years link the effect of herbal drugs specifically on ion channels, therefore the article primarily focuses on the effects of herbal drugs on ion channels, focusing on the role of ion channels, the difference in their structure, and the importance in the mechanism of action of herbal drugs. It is in the modern pharmacotherapy of neurological, cardiovascular and other diseases that herbal remedies are often included due to their ability to increase the effectiveness of traditional pharmacotherapy and low toxicity and cost. The purpose of the work – the goal of the work is to show the membranotropic effect of herbal drugs based on their effect on ion channels. Material and methods. Were performed an analysis of domestic and foreign literature and collected information from printed and online publications. Properties and types of potassium, calcium, and sodium channels are determined. Research results. The effect of herbal drugs on these channels, the connection with their pharmacological properties is shown. The ability of herbal drugs to influence potassium, calcium, and sodium channels indicates the membranotropic effect of the drugs. Conclusions. Thus, herbal drugs, as well as synthetic agents, can have a membranotropic effect, which explains their cardio and neurotropic effect. The membranotropic action of these agents is due mainly to the effect on potassium and calcium channels. Актуальність. У статті на підставі власних досліджень і джерел літератури наведені дані щодо впливу лікарських засобів рослинного походження, насамперед на іонні канали. Мембранотропна дія також пов’язана з рецепторами, ферментами, сигнальними системами. Разом із тим роботи останніх років пов’язують вплив рослинних препаратів саме на іонні канали, тому першочергово у статті акцентується увага на дії фітопрепаратів передусім на іонні канали, різниці їх структури і значенні в механізмі дії фітопрепаратів. Саме сучасну фармакотерапію неврологічних, серцево-судинних та інших хвороб часто доповнюють фітозасобами завдяки їх здатності підвищувати ефективність традиційної фармакотерапії і малої токсичності та вартості. Мета роботи – показати мембранотропну дію фітопрепаратів на підставі їх впливу на іонні канали. Методи дослідження. Був проведений аналіз вітчизняної і зарубіжної літератури, відомості з друкованих та інтернет-видань. Визначені властивості й види калієвих, кальцієвих, натрієвих каналів. Результати дослідження. Показано вплив фітопрепаратів на ці канали, зв’язок з їх фармакологічними властивостями. Можливості рослинних препаратів впливати на калієві, кальцієві, натрієві канали свідчать про мембранотропну дію препаратів. Висновки. Фітопрепарати, як і синтетичні засоби, можуть володіти мембранотропним впливом, що пояснює їх кардіота нейротропну дію. Мембранотропна дія цих засобів обумовлена здебільшого впливом на калієві та кальцієві канали.
Мембранотропна дія фітопрепаратів
Belenichev I. F. - ORCID: 0000-0003-1273-5314
Keywords: phytodrugs; potassium channels; calcium channels; sodium channels; membranotropic effect; фітопрепарати; калієві канали; кальцієві канали; натрієві канали; мембранотропна дія